2017
DOI: 10.1097/mcg.0000000000000805
|View full text |Cite
|
Sign up to set email alerts
|

Natural History and Treatment Outcomes of Severe Autoimmune Hepatitis

Abstract: Approximately 24% of patients with AIH have severe-AIH. Conventional autoantibodies are often absent in severe-AIH; however, it does not alter the outcome. Immunosuppressants should be given expediently in patients with severe-AIH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 35 publications
6
33
0
Order By: Relevance
“…This finding was corroborated in a French study, which used the same criteria to define AS‐AIH, where 10/17 (59%) patients developed ALF . A study from India suggested that the percentage of patients with AS‐AIH and ALF may be smaller …”
Section: Definitionsmentioning
confidence: 65%
See 2 more Smart Citations
“…This finding was corroborated in a French study, which used the same criteria to define AS‐AIH, where 10/17 (59%) patients developed ALF . A study from India suggested that the percentage of patients with AS‐AIH and ALF may be smaller …”
Section: Definitionsmentioning
confidence: 65%
“…Sonthalia et al compared a cohort of patients with severe AIH (including acute‐on‐chronic disease) and nonsevere AIH. The patients with severe AIH had histological features of centrilobular confluent necrosis without portal inflammation; however, these changes were also present in the nonsevere group . Other studies also identified centrilobular necrosis as a marker of severity in early and chronic AIH.…”
Section: Epidemiologymentioning
confidence: 92%
See 1 more Smart Citation
“…On the other hand, there are a few retrospective studies which have shown liver fibrosis to be an independent predictor of nonresponse to corticosteroids in AIH. A recent study by Sonthalia et al has shown hepatic encephalopathy to be one of the predictive markers of nonresponse in acute‐severe AIH …”
Section: Discussionmentioning
confidence: 99%
“…Acute AIH was defined as a patient having normal liver function or symptoms for >12 months or 26 weeks previously and only recently found to have abnormal function or symptoms for the first time. 7,8 Moreover, Dohmen et al…”
mentioning
confidence: 99%